2019
DOI: 10.1021/acsami.8b21410
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Viability and Functionality in Spatially Confined Microcavitation Zone

Abstract: Blast-induced traumatic brain injury (bTBI) can result in cell/tissue damage and lead to clinical and neuropsychiatric symptoms. Shock waves from a blast propagate through the brain and initiate cascades of mechanical and physiological events that can adversely affect the brain function. Although studies using animal models and brain slices have shown macroscale changes in the brain tissue in response to blast, systematic elucidation of coupling mechanisms is currently lacking. One mechanism that has been post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…We coined the term microcavitation to describe the process and was able to quantitatively study the interaction between brain endothelial cells and the collapse of highly pressurized microbubbles. The collapse of microbubbles (~55 kPa; ~10 s interaction time) was observed to detach cells from the substrate and created a region that is devoid of cells 35 . The area of cell detachment has been referred to as a crater.…”
Section: Discussionmentioning
confidence: 99%
“…We coined the term microcavitation to describe the process and was able to quantitatively study the interaction between brain endothelial cells and the collapse of highly pressurized microbubbles. The collapse of microbubbles (~55 kPa; ~10 s interaction time) was observed to detach cells from the substrate and created a region that is devoid of cells 35 . The area of cell detachment has been referred to as a crater.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the E-selectin expression was then examined in response to a mechanical trauma (microcavitation). One of the characteristics of this particular mechanical injury was shown to create a lesion in which the cells are detached following the collapse of highly pressurized microbubbles. ,, This mechanically induced event is explicitly demonstrated by the formation of approximately a circular area (∼100 μm diameter; Figure L) in which endothelial cells are detached. There are two observations to note.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for this significant difference in cell response before/after impact is that the amplitude of cavitation-induced pressure may be much larger than acceleration-induced pressure. However, a recent study reported that pressure associated with bubble collapse of thermally induced cavitation is about 56 kPa 19 , which is considerably smaller than the critical pressure, using a pressure sensitive film. Another possible mechanism is that cavitation-induced pressure, i.e., a rate of the pressure change in time, is much faster than acceleration-induced pressure and, as a result, viscoelastic response of cells, i.e., cell damage response, at different loading rates could be significantly different 28 .…”
Section: The Main Injury Mechanism: Cavitationmentioning
confidence: 91%
“…Dynamic cavitation in the brain is increasingly considered a potential damage mechanism for traumatic brain injury [16][17][18][19][20] . In this regard, one notable advance is in the characterization of cavitation properties for soft biomaterials under an impulsive force [21][22][23] .…”
Section: Mechanisms Of Cell Damage Due To Mechanical Impact: An In VImentioning
confidence: 99%